Growing Up With Disabilities: Education Law and the Transition to Adulthood - Clark, Susan; Lillie, Timothy (Disability Studies Quarterly, 2000)
The field of disability studies uses a social model or social construction model for much of its theoretical basis at present. The social model exists concurrently and, to some extent, is seen as replacing a civil rights approach. The authors propose that while the social model is very useful in understanding the nature of disability and should continue as a valuable theoretical underpinning, the civil rights model is better understood when educators are engaged in teaching children with disabilities what their rights are and how to exercise them. This is especially the case when considering students who are very cognitively impaired. An outline of the three most relevant US laws is given, along with information that is necessary for effective advocacy, whether by individuals with disabilities themselves or their families or friends.